A Solvent-Free Covalent Organic Framework Single-Ion Conductor Based on Ion–Dipole Interaction for All-Solid-State Lithium Organic Batteries - Li, Zhongping; Oh, Kyeong‑Seok; Seo, Jeong‑Min; Qin, Wenliang; Lee, Soohyoung; Zhai, Lipeng; Li, Changqing; Baek, Jong‑Beom; Lee, Sang‑Young (Nano-Micro Letters, 2024)
Single-ion conductors based on covalent organic frameworks (COFs) have garnered attention as a potential alternative to currently prevalent inorganic ion conductors owing to their structural uniqueness and chemical versatility. However, the sluggish Li+ conduction has hindered their practical applications. Here, we present a class of solvent-free COF single-ion conductors (Li-COF@P) based on weak ion–dipole interaction as opposed to traditional strong ion–ion interaction. The ion (Li+ from the COF)–dipole (oxygen from poly(ethylene glycol) diacrylate embedded in the COF pores) interaction in the Li-COF@P promotes ion dissociation and Li+ migration via directional ionic channels. Driven by this single-ion transport behavior, the Li-COF@P enables reversible Li plating/stripping on Li-metal electrodes and stable cycling performance (88.3% after 2000 cycles) in organic batteries (Li metal anode||5,5’-dimethyl-2,2’-bis-p-benzoquinone (Me2BBQ) cathode) under ambient operating conditions, highlighting the electrochemical viability of the Li-COF@P for all-solid-state organic batteries. Highlights: 1 A class of solvent-free covalent organic framework (COF) single-ion conductors (Li-COF@P) has been designed via ion–dipole interaction as opposed to traditional ion–ion interaction, promoting ion dissociation and Li+ migration through directional ionic channels. 2 The Li-COF@P enabled long cycle life (88.3% after 2000 cycles) in all-solid-state Li organic batteries (ASSLOBs) under ambient operating conditions, which outperformed those of previously reported ASSOLBs. 3 This Li-COF@P strategy holds promise as a viable alternative to the currently prevalent inorganic solid electrolytes.